Theoretical understanding of electronic and mechanical properties of 1T′ transition metal dichalcogenide crystals - Kazemi, Seyedeh Alieh; Imani Yengejeh, Sadegh; Wang, Vei; Wen, William; Wang, Yun (Beilstein Journal of Nanotechnology, 2022)
Transition metal dichalcogenides (TMDs) with a 1T′ layer structure have recently received intense interest due to their outstanding physical and chemical properties. While the physicochemical behaviors of 1T′ TMD monolayers have been widely investigated, the corresponding properties of layered 1T′ TMD crystals have rarely been studied. As TMD monolayers do not have interlayer interactions, their physicochemical properties will differ from those of layered TMD materials. In this study, the electronic and mechanical characteristics of a range of 1T′ TMDs are systematically examined by means of density functional theory (DFT) calculations. Our results reveal that the properties of 1T′ TMDs are mainly affected by their anions. The disulfides are stiffer and more rigid, diselenides are more brittle. In addition, the 1T′ polytype is softer than 2H TMDs. Comparison with the properties of the monolayers shows that the interlayer van der Waals forces can slightly weaken the TM–X covalent bonding strength, which can further influence the mechanical properties. These insights revealed by our theoretical studies may boost more applications of 1T′ TMD materials.
Keywords: 1T′ polytype; anisotropy; density functional theory; layered transition metal dichalcogenide crystals; shear modulus; Young’s modulus